Conflict of Moral in Syair Tenku Perabu (Malay Literature, 2024)
Literary works emerge as a medium that presents a variety of experiences, knowledge, and information with didactic purposes, serving multiple functions. One of these functions is related to the conflicts found in the Syair Tenku Perabu. This syair was written in the 19th century, and the identity of the original author remains unknown. The syair was composed as a form of challenge and protest against the highest authority, Sultan Hussein Muadzam Shah, who was the ruler of Singapore at that time. The main objective of this study is to discuss the conflicts present in Syair Tenku Perabu that sparked protests among the lower class society. To deepen the discussion, the concept of conflict by Abdullah Hassan and Ainon Mohd is used as the primary framework for analysis. According to Abdullah Hassan and Ainon (1998), there are three main triggers of conflict, which are negative behaviour, power, and relationship. They further added that there are two characteristics of conflict; content conflict, which centres around things, matters, events, or people that are the source of the conflict, and relational conflict, which involves individuals who have connections or relationships, such as spouses, children, or other family members. The findings of this study reveal that Syair Tenku Perabu is a work filled with conflictual elements, and the theory by Abdullah Hassan and Ainon Mohd appropriately applies to the analysis of this text.Full text: PDF